PENGARUH NITROGEN DAN FOSFOR TERHADAP PERTUMBUHAN DAN HASIL KEDELAI EDAMAME PADA TANAH GAMBUT - Iswiyanto, Andi; Radian, Radian; Abdurrahman, Tatang (Jurnal Sains Pertanian Equator, 2022)
Edamame soybeans contain antioxidants and isoflavones. Consumption of foods rich in antioxidants is associated with strengthening the body's immune system and reducing the risk of cancer. Application of N fertilizer to stimulate overall plant growth, is part of the plant cell itself, for the synthesis of amino acids and proteins in plants and stimulates vegetative growth. P fertilizer is useful for transporting energy from metabolism in plants, stimulating flowering and fruiting, stimulating root growth, stimulating seed formation, stimulating plant cell division and enlarging cell tissue. This study aims to determine the effect of applying N and P fertilizers and the interaction of N and P fertilizers on the growth and yield of edamame soybeans on peat soils. This study used a factorial Completely Randomized Design (CRD) consisting of 2 factors which were repeated 3 times. The first factor was N fertilizer consisting of 3 levels (n1: 50 kg/ha, n2: 100 kg/ha, n3: 150 kg/ha) and P fertilizer consisting of 3 levels (p1: 150 kg/ha, p2: 200 kg /ha, p3: 250 kg/ha Observational variables observed in this study were plant height, dry weight of plants, root volume, number of pods/plant, weight of pods/plant, weight of 100 seeds.Based on the research results that the interaction of N fertilizer and P fertilizer was able to affect plant height 2 WAP, but root volume, plant dry weight, plant height 3 WAP and 4 WAP, number of pods/plant, weight of pods/plant, and weight of 100 seeds had no significant effect and the same good growth was obtained. Keywords : nitrogen, phosphorus, soya bean, edamame, peat soil